Keeping an open mind: highlights and controversies of the breast cancer stem cell theory - Shah, M.; Allegrucci, Cinzia (Dove Medical Press, 2012)
The discovery that breast cancers contain stem-like cells has fuelled exciting research in the last few years. These cells are referred to as breast cancer stem cells (BCSCs) and are thought to be involved in tumor initiation, progression, and metastasis. Being intrinsically resistant to chemo- and radiotherapy, they are also considered responsible for recurrence of the disease after treatment. BCSCs have been suggested to be at the basis of tumor complexity, as they have the ability to self-renew and give rise to highly proliferating and terminally differentiated cancer cells that comprise the heterogeneous bulk of the tumor. There has been much speculation on the BCSC model, and in this review we address some fundamental questions, such as the identity of BCSCs and their involvement in tumor intra- and interheterogeneity. As an alternative to the BCSC model, we discuss clonal evolution, as both theories show extensive evidence in support of their arguments. Finally, we discuss a unifying idea that reconciles both models, which is based on stem cell plasticity and epigenetic modifications induced by the tumor microenvironment. The implications of cancer stem cell plasticity for drug discovery and future therapeutic interventions are presented.